Experimental energy and exergy analyses of ship refrigeration system operated by frequency inverter at varying sea water temperatures - Yilmaz, Oktay; Bayar, Haydar; Bashan, Veysi; Yigit, Kenan (SPRINGER HEIDELBERG, 2022)
Ship refrigeration compressors are sized to provide required capacity under extreme atmospheric and sea water temperatures, as well as full load and pulldown rates. Refrigeration compressors usually operate at 50-60 Hz in on/off mode at partial load in cold and temperate sea waters. The most efficient way to meet variable cooling demands is to change refrigerant mass flow by adjusting compressor speed. This paper is based on experimental investigation of ship cold storage refrigeration system on laboratory scale. Compressor is driven by inverter, and condenser is water-cooled type just like on ships. The refrigeration compressor has a power range of 600-1000 W and a maximum power of 1500 W. The system's refrigeration capacity ranges from 500 to 1350 W, with a maximum capacity of 2000 W. Experimental results were subjected to energy and exergy analyses. At 60 Hz, exergy efficiencies of compressor, condenser, expansion valve, and cold storage are 37.9%, 91.1%, 86.2%, and 69.8%, at - 5 degrees C cold storage and 18 degrees C water temperatures. In the same order, they contributed 73.2%, 7.6%, 10.4%, and 7% to wasted power. When water temperature increased from 18 to 35 degrees C at - 5 degrees C storage temperature and 50 Hz, coefficient of performance (COP) decreased by 55.2%. Despite compressor's thermodynamic irreversibility decreasing, combined electrical-mechanical efficiency deteriorated as frequency decreased. When compressor frequency was reduced from 60 to 40 Hz at - 5 degrees C cold storage and 18 degrees C water temperatures, COP increased by 13.9%.
Keywords: Marine refrigeration; Energy analysis; Exergy analysis; Coefficient of performance; Variable speed compressor; Sea water temperature; VARIABLE-SPEED COMPRESSOR; WASTE HEAT; PERFORMANCE EVALUATION; COOLING SYSTEM; SIMULATION; INJECTION; MODEL; PUMP; Engineering